Factors Related to the Incident of Pulmonary Tuberculosis in the Working Area of the Tarok Health Center Payakumbuh Citi West Sumatra Province 2023 - Husni, Virra; Putri, Fitria Eka; Nasution, Helmi Suryani (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Tuberculosis is a disease caused by the bacteria Mycobacterium tuberculosis. Tarok Health Center has the highest incidence rate of pulmonary TB in Payakumbuh City in 2022. In 2019 the CNR of TB cases was 178 per 100,000 populations. In 2020, the number of CNR TB cases was 112 per 100,000 populations. The CNR of TB in 2021 was 122 per 100,000 populations, in 2022 the CNR of TB cases will be 56 cases with a CNR of 284 per 100,000 populations. This research uses quantitative methods with case control methodology. The total sample was 88 samples; the research was carried out from September to October 2023 with analysis using the chi-square statistical test. This research shows that there is a relationship between ventilation area (0.005), humidity (0.031), temperature (0.029) and contact history (0.017) with the incidence of pulmonary TB in the working area of the Tarok Health Center, Payakumbuh City, then no relationship was found between floor type (=1) and residential density (0.052) and the incidence of pulmonary TB in the working area of the Tarok Health Center, Payakumbuh City.